2020
DOI: 10.1016/j.omto.2020.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Multivalent Aptamer Nanoparticles with Potential CAR-like Characteristics Could Activate T Cells and Inhibit Melanoma Growth

Abstract: In this study, the CAR-like multivalent aptamer nanoparticles (X-polymers) were assembled with the dimer of murine CD28 RNA aptamer (CD28Apt7), the tetramer of CTLA-4 (cytotoxic T-lymphocyte-associated protein 4) RNA aptamer (Del60), and a folic acid labeled ssDNA fragment in a stable nucleic acid three-way junction scaffold (3WJ). Results showed that the Xpolymers could recognize both the mCD28 and mCTLA-4 molecules. Confocal imaging and flow cytometry assays showed that the X-polymers could target both T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…Studies show that nanocarriers can efficiently introduce CAR genes into T cell nuclei, inducing tumor recognition and regression [ 117 , 156 , 157 , 158 , 159 ]. The experiments carried out by Bai et al (2020) [ 160 ] demonstrated that polymers of multivalent aptamers could fulfill the CAR-T function, since they were able to increase the proliferation of T cells, reverse the inhibitory effect of the secretion of antitumor cytokines, and inhibit the growth of mouse melanoma B16 cells both in vitro and in vivo [ 157 ]. The use of nanotechnology for the transient induction of CAR in T cells can also mitigate the side effects caused by the current method of using viral delivery vectors for the reprogramming of T lymphocytes [ 145 ].…”
Section: 3 T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies show that nanocarriers can efficiently introduce CAR genes into T cell nuclei, inducing tumor recognition and regression [ 117 , 156 , 157 , 158 , 159 ]. The experiments carried out by Bai et al (2020) [ 160 ] demonstrated that polymers of multivalent aptamers could fulfill the CAR-T function, since they were able to increase the proliferation of T cells, reverse the inhibitory effect of the secretion of antitumor cytokines, and inhibit the growth of mouse melanoma B16 cells both in vitro and in vivo [ 157 ]. The use of nanotechnology for the transient induction of CAR in T cells can also mitigate the side effects caused by the current method of using viral delivery vectors for the reprogramming of T lymphocytes [ 145 ].…”
Section: 3 T Cellsmentioning
confidence: 99%
“…The results of the study showed the ability of LNPs to deliver mRNA from the CAR to primary T cells and generate functional CAR T cells that have the potential to induce cancer cell death [ 159 ]. Furthermore, another approach to reprogramming T cells is to use nanocarriers to deliver drugs, antibodies, and interleukins, as they can protect T cells from immunosuppression and activate CD8+ T cells [ 160 , 161 , 162 , 163 , 164 ].…”
Section: 3 T Cellsmentioning
confidence: 99%
“…Similarly, in the last years, aptamers have been proven to act as immunoagents by themselves [80] or upon integration into immunomodulatory nanosystems [81]. Notably, the first CAR-like multivalent aptamer NPs were assembled that could activate T cells and inhibit melanoma growth, opening the way to use aptamer-based constructs for overcoming the safety issues of CAR-T cell therapy [82].…”
Section: Applications Of Aptamers In Cancer Targeted Therapymentioning
confidence: 99%
“…Bai et al developed CAR-like multivalent aptamer nanoparticles which were assembled with CD28 RNA aptamer and the tetramer of CTLA-4 RNA aptamer, as well as a folic acid labeled single stranded DNA fragment in a stable nucleic acid three-way junction scaffold. These nanoparticles increase T cell proliferation, reverse the inhibitory effect of IL-2 secreting caused by exogenous B7.1 molecules on T cells in vitro and promise a novel approach to develop a multi-functional design of aptamer drugs with potential CAR-like characteristics to enhance the safety of CAR-T cell immunotherapy ( 99 ).…”
Section: Applicable Systems Of Nanomodified Immunotherapymentioning
confidence: 99%